Differences in welfare take-up between immigrants and natives – a microsimulation study. Issue 2 (2nd May 2017) - Bruckmeier, Kerstin; Wiemers, Jürgen
Abstract : Purpose: International empirical evidence suggests that immigrants have a significantly higher risk than their native counterparts of being on welfare due to their observed characteristics. Nevertheless, it remains unclear if immigrants are also more prone to take-up benefits, conditional on being eligible. The authors explicitly focus on this potential explanation for higher welfare take-up rates. Therefore, the purpose of this paper is to analyze the take-up of social assistance in Germany by immigrants and natives, conditional on being eligible, and hence focus on take-up behavior rather than on determinants of eligibility. Design/methodology/approach: To simulate welfare entitlements, the authors employ a Tax-Transfer Microsimulation Model. It is a static microsimulation model that consists of a detailed implementation of the German tax and transfer system as well as an econometrically estimated labor supply model. After the simulation of welfare entitlements, the authors analyze take-up behavior within a discrete choice framework. The authors estimate probit models of observed welfare benefit take-up for the sample of eligible households taking into account unobserved heterogeneity. Findings: The estimation results do not reveal a significant effect of being a migrant on the probability of taking-up entitlements. The authors found a significant negative effect for citizens from European countries on the take-up probability, which disappeared after controlling for unobserved heterogeneity. Research limitations/implications: The authors find that it is worthwhile to focus on different groups of immigrants. Although not statistically significant, the rates of non-take-up of welfare benefits differ between different immigrant groups. The analysis further shows that controlling for unobserved heterogeneity is important when analyzing welfare differences between immigrants and natives. Practical implications: The higher welfare rates of immigrants are explained mainly by their higher risk of welfare dependence. Thus, given that reducing the welfare dependence of immigrants is a political goal, social policy measures to improve welfare recipients' labor market prospects are contested. However, restricting eligibility rules to reduce entitlements does not seem to be the appropriate measure, because the take-up probability does not differ between immigrants and natives after controlling for individual characteristics. Originality/value: The authors build on Castronova et al. (2001) and analyze the take-up behavior of individuals who are entitled to basic means-tested welfare benefits for employable persons in Germany. The analysis differs from Castronova et al. (2001) in four points. First, the authors provide first evidence of immigrant-native differences in welfare benefit take-up under the new welfare system in Germany after its reorganization in 2005. Second, the authors apply a microsimulation model of the comlete tax and transfer system in Germany to determine welfare eligibility. Third, the authors extend the analysis to a panel framework and take into account individual unobserved heterogeneity. Fourth, the authors distinguish between different groups of immigrants.